Anti-aging high-flame-retardant multifunctional rubber composite material and preparation method thereof
By using the use of a sibidane coupling agent in the rubber material in the rubber material, hydrolyzed the quantum dot layer of the metal phosphorhide complexes of the metal phosphorus composite of the metal phosphorus in the rubber material, solve the problem of aging of rubber materials during use, and achieve high flame retardant and excellent mechanical properties. , Extend the service life and reduce the cost.
Patent Information
- Application Number
- CN202411399431.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-09
AI Technical Summary
During use, existing rubber materials are susceptible to aging by factors such as heat, oxygen, ozone, light, mold, mechanical stress, etc., resulting in a decrease in mechanical properties and shortened service life, and it is difficult to take into account both aging resistance and high flame retardant properties.
The quantum dot plug -in -layer metal phosphorhide complex with a hydrolyzed sircin agent with a cymbal base is used for thermal pressure vulcanization of metal phosphones and rubber matriots to form a high -powered high flame -retardant multifunctional rubber composite material. This method uses a covalent and non -covalent way to uniformly disperse quantum dots and metal phosphones in the rubber matrix to capture free radicals to block aging reactions.
It has significantly improved the resistance, mechanics, flame retardant, abrasion and alkali -resistant corrosion performance of rubber composite materials, extended the service life, and reduced the cost of preparation. It has good industrialized production potential.
Smart Images

Figure CN119371723A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rubber composite materials, and in particular relates to an aging-resistant, highly flame-retardant, multifunctional rubber composite material and a preparation method thereof. Background Art
[0002] Due to the excellent mechanical properties of the three-dimensional network structure of rubber, it has been widely used in production and life, such as rubber tires, seals, damping systems, soft robots, wearable electronic devices and flexible sensors. However, during the use of rubber, it will be affected by physical, chemical and biological factors such as heat, oxygen, ozone, light, mold, mechanical stress, etc., which will cause oxidative degradation or structural reaction, causing the rubber to become soft, sticky, hard, cracked, moldy, change color, and reduce mechanical properties and gradually lose its use value. Therefore, improving the aging resistance of rubber is of great significance for practical applications and energy conservation and emission reduction.
[0003] At present, there are two methods for anti-aging treatment of rubber: physical protection and chemical protection. Among them, physical protection is mainly to avoid direct contact between rubber and various aging factors, such as surface coating or treatment. Usually, the use environment of rubber products is usually harsh, so the timeliness of physical protection is not high; chemical protection is mainly achieved by adding antioxidants, among which phenolic antioxidants have poor protective effects and will have an adverse effect on rubber vulcanization; amine antioxidants have a higher protective effect, but will cause rubber pollution and serious discoloration. In addition, the migration of antioxidants in the rubber matrix and their volatilization at high temperatures will cause a decrease in the anti-aging effect and even accelerate the aging of the rubber. Therefore, the development of new and efficient rubber anti-aging additives is of great significance and practical value.
[0004] Metal phosphides are a type of two-dimensional inorganic lamellar materials with excellent rigidity, stability, flame retardancy, and unique surface effects and quantum size effects. Filling these materials in rubber materials can not only enhance mechanical properties, thermal stability and acid and alkali corrosion resistance, but also give rubber many new functions. In recent years, metal phosphides have been widely reported in production practice and have great application value. However, simple physical mixing makes it difficult to control the uniform dispersion of metal phosphides in the rubber matrix, and the thermodynamic incompatibility between metal phosphides and rubber matrix may cause local stress concentration, thereby seriously damaging the mechanical properties of the material. Rubber products that can combine aging resistance and good mechanical properties have received full attention.
[0005] In addition, rubber is a flammable material. In daily life and specific application scenarios, such as rubber conveyor belts used in mines and rubber products used in vehicles and ships, they all need to have fire retardant properties to protect life and property. Therefore, in order to meet the diversified needs of production and life, prevent rubber from aging and degeneration, extend service life, and improve safety, it is urgent to develop a type of multifunctional rubber with excellent mechanical properties, aging resistance, and high flame retardant properties. Summary of the invention
[0006] The purpose of the present invention is to overcome the defects of the prior art and provide an aging-resistant, highly flame-retardant, multifunctional rubber composite material.
[0007] Another object of the present invention is to provide a method for preparing the above-mentioned aging-resistant, highly flame-retardant and multifunctional rubber composite material.
[0008] The technical scheme of the present invention is as follows: an aging-resistant, highly flame-retardant, multifunctional rubber composite material is prepared by uniformly mixing a rubber matrix, a quantum dot intercalated sheet metal phosphide composite as a filler and hydrolyzed and condensed with a silane coupling agent with a mercapto group, stearic acid, zinc oxide, a vulcanizing agent, an accelerator and paraffin, and then hot-pressing and vulcanizing the mixture. The general formula of the silane coupling agent with a mercapto group is HS-(CH 2 ) n -Si-OR 1 R 2 R 3 Among them, the quantum dot intercalated sheet metal phosphide complex hydrolyzed and condensed with the silane coupling agent with mercapto group is dispersed in the rubber matrix in a covalent and non-covalent manner; at the same time, the oxygen-containing and amine-containing groups on the surface of the above quantum dots capture the free radicals generated during the use of the rubber to block the aging phenomenon caused by the free radical chain reaction.
[0009] In a preferred embodiment of the present invention, the rubber matrix includes natural rubber, styrene-butadiene rubber and silicone rubber.
[0010] In a preferred embodiment of the present invention, the quantum dots include carbon quantum dots and boron nitride quantum dots.
[0011] In a preferred embodiment of the present invention, the lamellar metal phosphide includes lamellar zirconium phosphate, lamellar cobalt phosphate, lamellar iron phosphate and lamellar nickel phosphate.
[0012] In a preferred embodiment of the present invention, the rubber matrix includes natural rubber, styrene-butadiene rubber and silicone rubber, the quantum dots include carbon quantum dots and boron nitride quantum dots, and the lamellar metal phosphide includes lamellar zirconium phosphate, lamellar cobalt phosphate, lamellar iron phosphate and lamellar nickel phosphate.
[0013] Further preferably, the rubber matrix is natural rubber or styrene-butadiene rubber, the quantum dots are carbon quantum dots, and the lamellar metal phosphide is lamellar zirconium phosphate or lamellar iron phosphate.
[0014] More preferably, the silane coupling agent with terminal mercapto groups includes 3-mercaptopropyltrimethoxysilane and 3-mercaptopropyltriethoxysilane.
[0015] In a preferred embodiment of the present invention, the mass ratio of the rubber matrix, the quantum dot intercalated sheet metal phosphide complex as a filler and hydrolyzed and condensed with a silane coupling agent with a mercapto group, stearic acid, zinc oxide, vulcanizing agent, accelerator and paraffin is 60-100:10-80:1-3:2-4:1-4:1-3:1-3.
[0016] Further preferably, the mass ratio of the rubber matrix, the quantum dot intercalated sheet metal phosphide complex as a filler and hydrolyzed and condensed with a silane coupling agent with a mercapto group, stearic acid, zinc oxide, vulcanizing agent, accelerator and paraffin is 100:20:2:3:2.5:1:1.
[0017] The method for preparing the above-mentioned aging-resistant, highly flame-retardant, multifunctional rubber composite material is characterized by comprising the following steps:
[0018] (1) Stripping of metal phosphides;
[0019] (2) performing quantum dot intercalation on the sheet metal phosphide obtained in step (1), and performing hydrolysis condensation with a silane coupling agent with a mercapto group to obtain a quantum dot intercalated sheet metal phosphide composite hydrolyzed and condensed with a silane coupling agent with a mercapto group;
[0020] (3) uniformly mixing a rubber matrix, a quantum dot intercalated sheet metal phosphide complex hydrolyzed and condensed with a silane coupling agent having a mercapto group, stearic acid, zinc oxide, a vulcanizing agent, an accelerator and paraffin;
[0021] (4) hot-pressing and vulcanizing the material obtained in step (3) to obtain an aging-resistant, highly flame-retardant, multifunctional rubber composite material.
[0022] In a preferred embodiment of the present invention, the intercalation method includes physical blending intercalation and chemical covalent intercalation.
[0023] The beneficial effects of the present invention are:
[0024] 1. The quantum dots in the present invention have extremely high molar absorption coefficients in the ultraviolet region. The oxygen-containing and amine-containing groups on the surface can capture and remove oxygen-containing free radicals. 2The hybrid layer and aromatic ring conjugated structure can stabilize active electrons, effectively preventing the breakage and cross-linking of molecular chains caused by aging during the use of rubber, which in turn leads to cracks and fading of the rubber. In addition, the synergistic effect produced by the hybridization of metal phosphides and quantum dots can give rubber composites excellent mechanical, flame retardant, friction resistance and corrosion resistance.
[0025] 2. The present invention significantly expands the interlamellar spacing and improves the close stacking of the lamellae metal phosphides by using quantum dots to intercalate the lamellae metal phosphides, thereby achieving nanoscale dispersion in the rubber matrix, effectively avoiding local defects caused by adding large-sized lamellae metal phosphides to the rubber matrix, thereby causing stress concentration and serious damage to the mechanical properties; and significantly improves the interaction at the interface of the organic-inorganic components, that is, improves the interaction between the organic-inorganic components and the rubber matrix, giving the rubber composite material excellent mechanical properties.
[0026] 3. The quantum dots in the present invention are uniformly adsorbed on the surface of the lamellar metal phosphide and will not agglomerate due to standing or drying operations, and have excellent stability and durability; when added to the rubber matrix, due to the close combination between the quantum dots and the lamellar metal phosphide, the phenomenon of migration and volatilization from the rubber under high temperature, liquid environment, low pressure and other conditions is avoided.
[0027] 4. In the present invention, by controlling the amount of quantum dots added, the degree of exfoliation of the lamellar metal phosphide can be regulated, thereby regulating its dispersion and compatibility in the rubber matrix.
[0028] 5. In the present invention, by regulating the addition amount of the quantum dot intercalation sheet metal phosphide complex, the mechanical, flame retardant, wear resistance, acid and alkali corrosion resistance and aging resistance of the rubber composite material can be regulated in a wide range.
[0029] 6. The rubber composite material of the present invention has obvious modification effect, simple preparation process, mild preparation conditions, low cost and good industrial production potential.
[0030] 7. The effect of the quantum dot intercalated sheet metal phosphide complex in the present invention on improving the aging resistance of rubber is positively correlated with the double bond content in the rubber main chain; the quantum dot intercalated sheet metal phosphide complex and zinc oxide have a multi-element synergistic flame retardant effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is an optical photograph of the rubber prepolymer in Example 1 of the present invention.
[0032] Figure 2 This is the vulcanization curve of the rubber prepolymer in Example 1 of the present invention.
[0033] Figure 3This is an optical photograph of the rubber composite material in Example 1 of the present invention.
[0034] Figure 4 The SEM images of (a) α-ZrP in Example 1 of the present invention; and the TEM images of (b) E-ZrP and (c) CDs-ZrP.
[0035] Figure 5 1 is the XRD spectrum of α-ZrP, E-ZrP and CDs-ZrP in Example 1 of the present invention.
[0036] Figure 6 The UV-visible absorption spectra of CDs, E-ZrP and CDs-ZrP in Example 1 of the present invention. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is further illustrated and described below through specific implementation modes in combination with the accompanying drawings.
[0038] Example 1
[0039] (1) Exfoliation of lamellar zirconium phosphate (α-ZrP): 2 g of α-ZrP was dissolved in 50 mL of deionized water, 4 mL of exfoliating agent tetramethylammonium hydroxide (TMAH) was added, the mixture was stirred evenly, ultrasonically treated for 1 h, and then centrifuged for 10 min to obtain an exfoliated lamellar zirconium phosphate (E-ZrP) solution.
[0040] (2) Preparation of quantum dot intercalated zirconium phosphide complex: 4 mL of carbon quantum dot (CDs) (2 g) solution was added to 30 mL of the E-ZrP solution prepared in step (1), and the mixture was vigorously stirred at room temperature for 24 h, followed by centrifugation for 10 min and freeze-drying for 24 h. The resulting solid was hydrolyzed and condensed with 3-mercaptopropyltriethoxysilane under acidic conditions (pH = 3-5), and vacuum dried for 12 h to obtain a quantum dot intercalated zirconium phosphate complex CDs-ZrP.
[0041] (3) Evenly mixing rubber, quantum dot intercalation layer zirconium phosphide composite and other additives: by weight, 100 parts of natural rubber, 20 parts of CDs-ZrP prepared in step (2), 2 parts of stearic acid, 3 parts of zinc oxide, 2.5 parts of sulfur as a vulcanizing agent, 1 part of accelerator N-cyclohexyl-2-benzothiazole sulfenamide and 1 part of paraffin are mixed in an internal mixer for 8 minutes, and then the mixture is discharged through an open mixer to obtain a sheet as shown in FIG. Figure 1 The rubber prepolymer shown.
[0042] (4) Preparation of rubber composite material: Weigh 3.5 g of the rubber prepolymer prepared in step (3) and test the vulcanization curve (such as Figure 2As shown), the positive vulcanization time is determined to be 12.9 minutes, and the plate hot press is hot-pressed at 15MPa pressure and 150°C for 12.9 minutes to obtain the following Figure 3 The aging-resistant and highly flame-retardant multifunctional rubber composite material shown.
[0043] Example 2
[0044] The difference between this embodiment and embodiment 1 is that natural rubber is replaced by styrene-butadiene rubber. By weight, 100 parts of styrene-butadiene rubber, 20 parts of CDs-ZrP, 2 parts of stearic acid, 3 parts of zinc oxide, 2.5 parts of sulfur, 1 part of N-cyclohexyl-2-benzothiazole sulfenamide and 1 part of paraffin are mixed in an internal mixer for 8 minutes and then sheeted by an open mixer to obtain a rubber prepolymer.
[0045] The remaining steps are the same as those in Example 1 to obtain the aging-resistant, highly flame-retardant, multifunctional rubber composite material.
[0046] Example 3
[0047] The difference between this embodiment and embodiment 1 is that the lamellar zirconium phosphate in step (1) and step (2) is replaced by lamellar iron phosphate. Specifically, the stripping of lamellar iron phosphate: 2g of lamellar iron phosphate is dissolved in 50mL of deionized water, 4mL of stripping agent tetramethylammonium hydroxide (TMAH) is added, stirred evenly, ultrasonically treated for 1h, and then centrifuged for 10min to obtain a stripped lamellar iron phosphate solution. Preparation of quantum dot intercalated lamellar iron phosphate complex: 4mL of carbon quantum dots (CDs) (2g) solution is added to 30mL of the stripped lamellar iron phosphate solution, vigorously stirred for 24h at room temperature, then centrifuged for 10min and freeze-dried for 24h, the resulting solid is hydrolyzed and condensed with 3-mercaptopropyltriethoxysilane under acidic conditions (pH=3-5), and vacuum dried for 12h to obtain a quantum dot intercalated iron phosphate complex. In parts by weight, 100 parts of natural rubber, 20 parts of quantum dot intercalated iron phosphate complex, 2 parts of stearic acid, 3 parts of zinc oxide, 2.5 parts of sulfur, 1 part of N-cyclohexyl-2-benzothiazole sulfonamide and 1 part of paraffin are kneaded in an internal mixer for 8 minutes, and then sheeted out through an open mixer to obtain a rubber prepolymer.
[0048] The preparation method of the quantum dot intercalated iron phosphate modified natural rubber composite material described in this embodiment is the same as that in Example 1.
[0049] Comparative Example 1
[0050] The difference between this comparative example and Example 1 is that step (2) is omitted. By weight, 100 parts of natural rubber, 20 parts of E-ZrP, 20 parts of CDs, 2 parts of stearic acid, 3 parts of zinc oxide, 2.5 parts of sulfur, 1 part of N-cyclohexyl-2-benzothiazole sulfenamide, and 1 part of paraffin are mixed in an internal mixer for 8 minutes and then sheeted through an open mixer to obtain a rubber prepolymer.
[0051] The rest was the same as in Example 1 to prepare a comparative rubber composite material.
[0052] Comparative Example 2
[0053] The difference between this comparative example and Example 2 is that step (2) is omitted. By weight, 100 parts of styrene-butadiene rubber, 20 parts of E-ZrP, 20 parts of CDs, 2 parts of stearic acid, 3 parts of zinc oxide, 2.5 parts of sulfur, 1 part of N-cyclohexyl-2-benzothiazole sulfenamide and 1 part of paraffin are mixed in an internal mixer for 8 minutes and then sheeted through an open mixer to obtain a rubber prepolymer.
[0054] The remaining steps were the same as those in Example 1 to prepare a comparative rubber composite material.
[0055] Comparative Example 3
[0056] The difference between this comparative example and Example 1 is that the lamellar zirconium phosphate in step (1) is replaced by lamellar iron phosphate (see Example 3 for details), and step (2) is omitted. In parts by weight, 100 parts of natural rubber, 20 parts of stripped iron phosphate, 20 parts of CDs, 2 parts of stearic acid, 3 parts of zinc oxide, 2.5 parts of sulfur, 1 part of N-cyclohexyl-2-benzothiazole sulfenamide and 1 part of paraffin are mixed in an internal mixer for 8 minutes, and then sheeted through an open mixer to obtain a rubber prepolymer.
[0057] The remaining steps were the same as those in Example 1 to prepare a comparative rubber composite material.
[0058] Comparative Example 4
[0059] The difference between this comparative example and Example 1 is that step (2) is omitted and CDs is not added. By weight, 100 parts of natural rubber, 20 parts of E-ZrP, 2 parts of stearic acid, 3 parts of zinc oxide, 2.5 parts of sulfur, 1 part of N-cyclohexyl-2-benzothiazolesulfenamide, and 1 part of paraffin are mixed in an internal mixer for 8 minutes and then sheeted through an open mixer to obtain a rubber prepolymer.
[0060] The remaining steps were the same as those in Example 1 to prepare a comparative rubber composite material.
[0061] Comparative Example 5
[0062] The difference between this comparative example and Example 2 is that step (2) is omitted and CDs is not added. By weight, 100 parts of styrene-butadiene rubber, 20 parts of E-ZrP, 2 parts of stearic acid, 3 parts of zinc oxide, 2.5 parts of sulfur, 1 part of N-cyclohexyl-2-benzothiazole sulfenamide, and 1 part of paraffin are mixed in an internal mixer for 8 minutes and then sheeted through an open mixer to obtain a rubber prepolymer.
[0063] The remaining steps were the same as those in Example 2 to prepare a comparative rubber composite material.
[0064] Comparative Example 6
[0065] The difference between this comparative example and Example 1 is that 3-mercaptopropyltriethoxysilane in step (2) is replaced by γ-aminopropyltriethoxysilane. In parts by weight, 100 parts of natural rubber, 20 parts of carbon quantum dot intercalated layer zirconium phosphide composite, 2 parts of stearic acid, 3 parts of zinc oxide, 2.5 parts of sulfur, 1 part of N-cyclohexyl-2-benzothiazolesulfonamide, and 1 part of paraffin are mixed in an internal mixer for 8 minutes and then sheeted through an open mixer to obtain a rubber prepolymer.
[0066] The remaining steps were the same as those in Example 1 to prepare a comparative rubber composite material.
[0067] Comparative Example 7
[0068] The difference between this comparative example and Example 1 is that the sheet zirconium phosphate is replaced by sheet graphene. After the graphene is mechanically peeled off by a mortar, 4 mL of carbon quantum dots (CDs) (2 g) solution is added to 30 mL of graphene aqueous solution, and the mixture is vigorously stirred for 24 h at room temperature, followed by centrifugation for 10 min and freeze-dried for 24 h. The obtained solid is hydrolyzed and condensed with 3-mercaptopropyltriethoxysilane under acidic conditions (pH = 3-5), and vacuum dried for 12 h to obtain a quantum dot intercalated graphene composite. By weight, 100 parts of natural rubber, 20 parts of quantum dot intercalated graphene composite, 2 parts of stearic acid, 2.5 parts of sulfur, 1 part of N-cyclohexyl-2-benzothiazole sulfonamide, and 1 part of paraffin are mixed in a mixer for 8 min, and then the rubber prepolymer is obtained by sheeting through an open mixer.
[0069] The remaining steps were the same as those in Example 1 to prepare a comparative rubber composite material.
[0070] Example 4
[0071] The following performance tests were performed on Examples 1 to 3 of the present invention and Comparative Examples 1 to 4, and the test items and methods are as follows:
[0072] Hardness test: According to the method specified in GB / T 531.1-2008, the hardness of the rubber composite material prepared as above was measured.
[0073] Stress-strain property test: According to the method specified in GB / T 528-2009, the 100% modulus stress, 300% modulus stress, tensile strength and elongation at break of the rubber composite material prepared as above were measured.
[0074] Combustion performance test: According to the method specified in GB / T 10707-2008, the limiting oxygen index and vertical combustion grade of the rubber composite material prepared as above were measured.
[0075] UV aging resistance test: According to the method specified in GB / T 16585-1996, the sample is placed in a UV aging box and exposed to UV radiation for 70 days. The mechanical properties of the aged sample are determined according to the above stress-strain performance test method, and the performance change rate of the sample is calculated.
[0076] All test results are shown in Tables 1 and 2 below.
[0077] Table 1. Experimental characterization results of samples 1 to 3
[0078]
[0079]
[0080] Table 2. Experimental characterization results of comparative samples 1 to 7
[0081]
[0082] Experimental data analysis:
[0083] The morphology of the unpeeled zirconium phosphate α-ZrP was observed by SEM ( Figure 4 (a) The original α-ZrP has a polygonal structure with a diameter of about 1 μm, a smooth surface and close stacking between the layers. The exfoliated zirconium phosphate E-ZrP and the quantum dot intercalated zirconium phosphate CDs-ZrP were characterized by TEM, as shown in Figure 2. Figure 4 As shown in (b), the regularity of the shape of E-ZrP decreased and the thickness became thinner, indicating that the stacking of zirconium phosphate sheets was improved. Figure 4 (c) The layered skeleton structure of the material is maintained, the agglomeration between the layers is further improved, and uniformly attached CDs are observed on the surface of the material.
[0084] The crystal structures of α-ZrP, E-ZrP and CDs-ZrP were further characterized by XRD. Figure 5 As shown, α-ZrP shows good crystallinity. According to the Bragg equation, the interlayer spacing of α-ZrP is (2θ=11.70°); after exfoliation treatment, the (002) crystal plane diffraction peak of E-ZrP shifts to the left at 2θ=5.50°, which is due to the stripping agent TMAH cation sandwiched between the zirconium phosphate flakes; after CDs intercalation hybridization, the (002) crystal plane diffraction peak angle of CDs-ZrP shifts to 2θ=4.65°, indicating that the interlayer spacing of zirconium phosphate CDs-ZrP after quantum dot intercalation is further increased, which greatly reduces the stacking between zirconium phosphate flakes.
[0085] The UV-visible absorption spectra of E-ZrP, CDs and CDs-ZrP are shown in Figure 6 As shown. CDs showed characteristic absorption peaks at 220nm, 240nm and 281nm, which were related to the n-π* transition of C=N in quantum dots, the π-π* transition of C=C on the benzene ring and the n-π* transition of N-containing functional groups, respectively. Compared with E-ZrP, the UV-visible absorption spectrum of CDs-ZrP intercalated with zirconium phosphate showed characteristic absorption peaks belonging to quantum dots. The results showed that zirconium phosphate was successfully intercalated and hybridized by CDs, giving CDs-ZrP good ultraviolet absorption ability.
[0086] The test data of the above-mentioned embodiments 1 to 3 and comparative examples 1 to 7 are shown in Tables 1 and 2 above. From the test results, it can be seen that the 100% tensile stress of Examples 1, 2 and 3 treated with quantum dots is greater than 3.2 MPa, the 300% tensile stress is greater than 12.3 MPa, the tensile strength is greater than 27.9 MPa, and the elongation at break is greater than 515%. Compared with comparative examples 1 to 3 prepared by simple blending, the mechanical properties are greatly improved. This is attributed to the fact that the quantum dot intercalation process improves the stacking of the metal phosphide sheets, improves its dispersion compatibility in the rubber matrix, and significantly improves the interface interaction with the rubber matrix; the limiting oxygen index of Examples 1 to 3 is greater than 28.4%, and the vertical combustion performance reaches the FV-0 flame retardant grade, which can meet the flame retardant use requirements of various rubber tires and conveyor belts for rubber composite materials.
[0087] The limiting oxygen index of comparative examples 1 to 3 is 24.5 to 25.3%, and the vertical combustion performance is all FV-2 flame retardant grade, which indicates that compared with the simple blending of quantum dots and lamellar metal phosphides, the synergistic effect produced by the quantum dots intercalated with lamellar metal phosphides can improve the flame retardant performance.
[0088] After all samples were artificially treated with ultraviolet aging for 70 days, the ultraviolet aging resistance of the samples was evaluated by comparing the stress and strain change rates of the samples before and after ultraviolet aging. The stress change rates of Examples 1 to 3 were all less than 13.3%, and the strain change rates were all less than 16.4%. The ultraviolet aging resistance of Comparative Examples 1 to 3 was significantly reduced. Since Comparative Example 4 did not contain quantum dots, the stress and strain change rates of the samples after ultraviolet aging treatment were both greater than 79.4%. By comparing Examples 1 and 2 with Comparative Examples 4 and 5 without adding carbon quantum dots, it was found that since there are more unsaturated double bonds on the main chain of natural rubber, adding quantum dot intercalated sheet metal phosphide in natural rubber has a higher anti-aging performance improvement.
[0089] The effect of the terminal group structure of the silane coupling agent on the mechanical properties of the rubber composite material was investigated: the quantum dot intercalated sheet metal phosphide complex was surface silanized using γ-aminopropyltriethoxysilane (the terminal group is an amine group), and a natural rubber composite material was prepared (Comparative Example 6). Compared with Example 1, the mechanical properties of the amine-modified composite material showed a certain degree of decline. This is because the thiol group in Example 1 can undergo addition reaction with the double bonds on the rubber main chain, and the inorganic filler is dispersed in the rubber matrix in a covalent and non-covalent manner, thereby enhancing the interaction strength between the inorganic filler and the rubber matrix, thereby improving the mechanical properties of the rubber composite material.
[0090] A composite rubber material (Comparative Example 7) in which lamellar graphene is used instead of lamellar metal phosphide is prepared, and its flame retardant properties are tested. Its vertical burning grade is N and LOI is 20.4%. Compared with Example 1 (LOI 29.8%), its flame retardant properties are greatly reduced, which indicates that the quantum dot intercalated lamellar metal phosphide in Example 1 plays an important flame retardant role, and the multi-element synergistic effect between zinc oxide and quantum dot intercalated lamellar metal phosphide promotes further improvement of the flame retardant effect.
[0091] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. An aging-resistant, highly flame-retardant, multifunctional rubber composite material, characterized by: The invention is prepared by mixing a rubber matrix, a quantum dot intercalated sheet metal phosphide complex as a filler and hydrolyzed and condensed with a silane coupling agent with a mercapto group, stearic acid, zinc oxide, a vulcanizing agent, an accelerator and paraffin, and then hot-pressing and vulcanizing the mixture. The general formula of the silane coupling agent with a mercapto group is HS-(CH2) n -Si-O-R1R2R3, wherein the quantum dot intercalated sheet metal phosphide complex hydrolyzed and condensed with a silane coupling agent with a mercapto group is dispersed in the rubber matrix in a covalent and non-covalent manner; at the same time, the oxygen-containing and amine-containing groups on the surface of the above quantum dots capture the free radicals generated during the use of the rubber to block the aging phenomenon caused by the free radical chain reaction.
2. The aging-resistant, highly flame-retardant, multifunctional rubber composite material according to claim 1, characterized in that: The rubber matrix includes natural rubber, styrene-butadiene rubber and silicone rubber.
3. The aging-resistant, highly flame-retardant, multifunctional rubber composite material according to claim 1, characterized in that: The quantum dots include carbon quantum dots and boron nitride quantum dots.
4. The aging-resistant, highly flame-retardant, multifunctional rubber composite material according to claim 1, characterized in that: The lamellar metal phosphide includes lamellar zirconium phosphate, lamellar cobalt phosphate, lamellar iron phosphate and lamellar nickel phosphate.
5. The aging-resistant, highly flame-retardant, multifunctional rubber composite material according to claim 1, characterized in that: The rubber matrix includes natural rubber, styrene-butadiene rubber and silicone rubber, the quantum dots include carbon quantum dots and boron nitride quantum dots, and the lamellar metal phosphide includes lamellar zirconium phosphate, lamellar cobalt phosphate, lamellar iron phosphate and lamellar nickel phosphate.
6. The aging-resistant, highly flame-retardant, multifunctional rubber composite material according to claim 1, characterized in that: The silane coupling agent with mercapto group includes 3-mercaptopropyltrimethoxysilane and 3-mercaptopropyltriethoxysilane.
7. An aging-resistant, highly flame-retardant, multifunctional rubber composite material according to any one of claims 1 to 6, characterized in that: The mass ratio of the rubber matrix, the quantum dot intercalated sheet metal phosphide complex as filler and hydrolyzed and condensed with a silane coupling agent with a mercapto group, stearic acid, zinc oxide, vulcanizing agent, accelerator and paraffin is 60-100:10-80:1-3:2-4:1-4:1-3:1-3.
8. The aging-resistant, highly flame-retardant, multifunctional rubber composite material according to claim 7, characterized in that: The mass ratio of the rubber matrix, the quantum dot intercalated sheet metal phosphide complex as filler and hydrolyzed and condensed with a silane coupling agent with a mercapto group, stearic acid, zinc oxide, a vulcanizing agent, an accelerator and paraffin is 100:20:2:3:2.5:1:
1.
9. The method for preparing an aging-resistant, highly flame-retardant, multifunctional rubber composite material according to any one of claims 1 to 8, characterized in that: The steps include: (1) Stripping of metal phosphides; (2) performing quantum dot intercalation on the sheet metal phosphide obtained in step (1), and performing hydrolysis condensation with a silane coupling agent with a mercapto group to obtain a quantum dot intercalated sheet metal phosphide composite hydrolyzed and condensed with a silane coupling agent with a mercapto group; (3) uniformly mixing a rubber matrix, a quantum dot intercalated sheet metal phosphide complex hydrolyzed and condensed with a silane coupling agent having a mercapto group, stearic acid, zinc oxide, a vulcanizing agent, an accelerator and paraffin; (4) hot-pressing and vulcanizing the material obtained in step (3) to obtain an aging-resistant, highly flame-retardant, multifunctional rubber composite material.
10. The preparation method according to claim 9, characterized in that: The intercalation method includes physical blending intercalation and chemical covalent intercalation.
Citation Information
Patent Citations
Halogen-free flame-retardant reinforced addition liquid silicone rubber and preparation method thereof
CN104774474A
Peeling method for laminated material and peeled material acquired by peeling
CN106512886A
Anti-aging nitrile butadiene rubber composite based on functional zirconium phosphate modification and preparation method thereof
CN109134971A
Flame-retardant cable and preparation method thereof
CN118271737A
Vulcanized, silicone rubber composition, combustion modifier, rocket motor, and propellant grain
JP1992015258A